Embracing Powerlessness in Pursuit of Digital Resilience: Managing Cyber-Literacy in Professional Talk. (November 2015) - Hammond, Simon P.; Cooper, Neil J.
The use of digital media by adolescents living in out-of-home care raises safeguarding and risk-management concerns, creating challenges for practitioners in how to control risk while promoting independence. This article explores how professionals working in residential care negotiated their own and adolescents' use of ubiquitous digital phenomena. Extracts from everyday conversations occurring during a participatory research project working with adolescents and carers in four English residential care homes are discursively analyzed to demonstrate how professionals drew on socially available resources to construct digital media usage. Analysis demonstrates an orientation toward mobilizations of powerlessness as accepted, the usefulness of constructing digital competency as a function of generation, and the need for professionals to embrace powerlessness. Adopting a position of embraced powerlessness accepts the inability to halt access and use of digital technologies. This position enabled workers to facilitate opportunities for digital resilience development in vulnerable adolescents.